2001
DOI: 10.1007/s004050100330
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of sites of sleep-induced upper airway obstruction. A 2-night study based on recordings of airway pressure and flow

Abstract: Repeatability of sites of obstructive events is influenced by the severity of illness and the degree of upper or lower obstructive predominance. The distribution of sites of obstructive events (classified as mainly "upper"/"lower" or as percent upper obstructive events of all) can be identified with relative confidence in patients who have frequent apneic events (AI > or = 5) or a high degree of upper or lower obstructive predominance and especially in those who have a combination of these two criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
(19 reference statements)
1
14
0
1
Order By: Relevance
“…These results suggest that the AG systems provide the possibility of studying the features of obstruction in short daytime and nocturnal sleep. It is similar to the results of previous study that overnight continuous recording of airway pressure and flow is a relatively new good method for measuring apneic and hypopneic events [4,12]. The main findings of the present study indicate that there was no significant difference between dAG and nAG with regard to the main indices of sleep disorder events (AHI, AI, CAHI, MAHI, OAHI).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that the AG systems provide the possibility of studying the features of obstruction in short daytime and nocturnal sleep. It is similar to the results of previous study that overnight continuous recording of airway pressure and flow is a relatively new good method for measuring apneic and hypopneic events [4,12]. The main findings of the present study indicate that there was no significant difference between dAG and nAG with regard to the main indices of sleep disorder events (AHI, AI, CAHI, MAHI, OAHI).…”
Section: Discussionsupporting
confidence: 93%
“…But all these methods are controversial for correlating poorly with collapse observed during sleep. The need for an alternative diagnostic tool that can be used to identify the exact location of the airway obstruction led to the development of the ApneaGraph (AG) [4,5]. The AG200 ApneaGraph system (MRA Medical, UK) is a new method for diagnosing obstructive sleep-related breathing disorders (SRDB) and identifying sites of obstruction [6].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of the type of obstruction as well as the localization of the predominant site of narrowing may be critical in determining the appropriate treatment of these patients. Some of the disappointing results that have been reported after sleep-related surgeries in patients with obstructive sleep apnea syndrome (OSAS) may be due to a lack of reliable methods for localization of the functionally relevant upper airway narrowing [1][2][3][4] . Over recent years, there is an increased requirement for an innovative outpatient sleep diagnostic tool, which should be similar to a polysom-nography (PSG) sleep study and help to localize the level of the upper airway obstruction in patients suffering from SRBD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the use of continuous airway pressure and flow monitoring is reproducible [16], and that AG and polysomnography are not significantly different for measuring the AHI, the total number of apneic events, ASaO 2 , and LSaO 2 [17]. We used the following definitions of OSAHS: mild, AHI ≥5 and ≤15; moderate, AHI >15 and ≤30; and severe, AHI >30.…”
Section: Ag Pressure Measurementsmentioning
confidence: 99%